Community forest rights in Nigeria - Recommendations for CSOs - Allen, F.; Ojo, G.U.; Offiong, R.A. (2020)
As part of a multi-country review of community forest rights, Environmental Rights Action/Friends of the Earth Nigeria conducted a review of community forest rights in Nigeria. In this policy brief we summarize some of the main outcomes of the review, and the consequent recommendations for CSOs.